Pengembangan Perangkat Pembelajaran Biologi Bernuansa Imtaq Pada Materi Sistem Reproduksi Manusia Untuk Siswa MAN - Nilpia Eldalisna (Universitas Hamzanwadi, 2024)
Teacher does not use IMTAQ teaching aids yet. It is not integrated into learning. The teacher would like asses on cognitive aspects rather than the affactive or moral aspec so that attitudes of the students continue to decline. The research is to produce IMTAQ Teaching Aids in form of syllabus, lesson plans, modules, materials and worksheets for reproduction system intended for Madrasah Aliyah students in learning Biology. The observation was very effective categorized. In short, IMTAQ Teaching Aids for Reproduction System Material Intended for Madrasah Aliyah students in learning Biology are valid, practical and effective